Intelligent controlled-release core-shell alginate soil conditioner and preparation method thereof
By adopting the intelligent controlled release core-shell-type alginate soil conditioner designed with a three-layer core-shell-layer structure, the problems of single functions and poor environmental responsiveness in the existing technology are solved, and the synergistic function of controlled nutrient release and heavy metal adsorption is realized. The nutrient release is synchronized with the crop growth cycle through multiple response mechanisms, which significantly improves the soil improvement effect and nutrient utilization efficiency.
Patent Information
- Application Number
- CN202510661328.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-22
AI Technical Summary
The existing soil conditioner has a single function, and it is difficult to achieve the synergistic effect of controlled nutrient release and heavy metal adsorption at the same time. It also has poor environmental responsiveness, complex preparation process, and poor product uniformity and stability.
The intelligent controlled release core-shell-type alginate soil conditioner designed with a three-layer core-shell-layer structure is used to achieve the synergistic function of controlled nutrient release and heavy metal adsorption through the combination of improved alginate, chitosan and nanomaterials, and the nutrient release is synchronized with the crop growth cycle through the pH/temperature/microbial triple response mechanism.
It has achieved accurate nutrient supply, efficient fixation of heavy metals and soil microenvironment regulation, significantly improved nutrient utilization efficiency and soil improvement effect, and improved product stability and uniformity, and is suitable for different soil environments.
Smart Images

Figure CN120172793A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an intelligent controlled-release core-shell alginate soil conditioner and a preparation method thereof, specifically to a multifunctional composite soil conditioner with a core-shell-layer three-layer structure, belonging to the technical fields of agricultural soil improvers, environmental remediation materials, and controlled-release fertilizers. Background Art
[0002] With the growth of the global population and the intensification of environmental pollution, agricultural production is facing severe challenges. Soil problems such as nutrient deficiency, heavy metal pollution, salinization, etc. have become important factors restricting the sustainable development of agriculture. Traditional soil conditioners and fertilizers often have problems such as low use efficiency, fast loss, and great environmental harm.
[0003] Soil heavy metal pollution is one of the major environmental problems worldwide. According to research, the area of arable land contaminated by heavy metals in China reaches 20 million hectares, and the exceeding rates of cadmium and lead sites are 7% and 1.5% respectively, which are relatively serious toxic elements in the environment. Heavy metal pollution not only reduces soil quality and crop yields, but also poses a serious threat to human health.
[0004] To solve these problems, controlled-release fertilizers and multifunctional soil conditioners have emerged as the times require. Traditional controlled-release fertilizers mainly achieve slow release of nutrients through methods such as polymer coating and ion exchange, but have problems such as high cost, low nutrient utilization efficiency, and non-environmentally friendly degradation products. As an environmentally friendly alternative, bio-based controlled-release materials are receiving increasing attention.
[0005] Chitosan, as a natural polysaccharide, has good biodegradability, biocompatibility, and antibacterial activity. Its molecular chain contains a large number of active groups such as amino and hydroxyl groups, which can chelate and adsorb heavy metal ions. Alginate is a natural anionic polysaccharide extracted from seaweed, with good gel performance and biocompatibility. These two materials have been widely used in the fields of drug delivery, tissue engineering, etc.
[0006] Japanese Patent JPH0713233B2, titled "Soil Conditioner", describes a soil conditioner containing chitosan, which is mainly used to improve the physical and chemical properties of the soil, but its gel structure is simple and does not have the synergistic functions of nutrient controlled release and heavy metal adsorption. Chinese Patent CN104311253A, titled "Chitosan Controlled-Release Fertilizer Microspheres and Preparation Method Thereof", discloses a controlled-release fertilizer microsphere composed of chitosan and sodium alginate, but its preparation method is complex, the product stability is poor, and it cannot achieve multiple environmentally responsive release.
[0007] In recent years, core-shell structured materials have received extensive attention due to their unique properties. The core-shell structure can integrate different functions into the same material to achieve the synergistic effect of multiple functions. However, most of the core-shell structured soil conditioners in the existing technology are prepared by complex emulsification methods, which not only have complex processes and high costs, but also have uneven particle size distribution and poor stability of the products, making it difficult to achieve precise controlled release.
[0008] As a new type of particle preparation method, electrospray technology has the advantages of simple operation, controllable particle size, and good product uniformity, and has been applied in the field of drug delivery. Coaxial electrospray technology can achieve the one-step preparation of microcapsules with complex structures, providing a new idea for the preparation of multifunctional soil conditioners.
[0009] According to the researchers, chitosan and alginate can form a complex through electrostatic interaction to enhance the mechanical properties and stability of the material. In addition, chitosan / alginate composite materials show excellent controlled release performance in drug delivery systems, but this property has not been fully applied in the field of soil conditioners.
[0010] In summary, the existing soil conditioners have the following deficiencies: 1. Single function, it is difficult to simultaneously achieve the synergistic effect of nutrient controlled release and heavy metal adsorption; 2. Poor environmental responsiveness, unable to achieve intelligent controlled release according to soil environmental changes; 3. Complex preparation process, with poor product uniformity and stability; 4. The degradation products of the materials may cause secondary pollution to the environment.
[0011] Therefore, developing a multifunctional soil conditioner with controllable structure, synergistic functions, and environmental friendliness is of great significance for improving agricultural production efficiency, repairing polluted soils, and promoting sustainable agricultural development. Summary of the Invention
[0012] The purpose of the present invention is to provide an intelligent controlled release core-shell type alginate soil conditioner and its preparation method to solve the problems existing in the existing technology. This conditioner adopts a three-layer core-shell-layer structure design to achieve the synergistic functions of nutrient controlled release and heavy metal adsorption, and through a multiple environmental response mechanism, the nutrient release is synchronized with the crop growth cycle, significantly improving the nutrient utilization efficiency and soil improvement effect.
[0013] The purpose of the present invention is to provide an intelligent controlled release core-shell type alginate soil conditioner, which has a three-layer core-shell-layer structure and includes the following components in weight percentage: A. The core layer accounts for 30% of the total weight and includes: a) 50-60% of modified alginate; b) 10-15% of humic acid; c) 20 - 25% of nitrogen, phosphorus and potassium compound nutrients; d) 3 - 5% of trace elements; e) 5 - 10% of auxiliary materials; B. The middle shell layer accounts for 40% of the total weight and includes: a) 40 - 50% of chitosan with a deacetylation degree greater than or equal to 90%; b) 10 - 15% of gelatin; c) 15 - 20% of nanozeolite or montmorillonite; d) 5 - 10% of microbial agents; e) 5 - 10% of poly (lactic - co - glycolic acid); f) 5 - 10% of auxiliary materials; C. The outer layer accounts for 30% of the total weight and includes: a) 40 - 50% of modified biochar; b) 20 - 30% of bentonite; c) Magnetic nano particles 5 - 10%; d) 5 - 10% of cross - linking agents; e) 10 - 15% of auxiliary materials.
[0014] Preferably, the M / G ratio of the modified alginate is 1.2 - 1.5, the viscosity of the 1% aqueous solution is greater than or equal to 300 mPa·s, and the organic matter content is 35 - 45%.
[0015] Preferably, the microbial agent includes at least one of Azospirillum brasilense, Bacillus subtilis and white - rot fungi, wherein the viable count of Azospirillum brasilense is greater than or equal to , the viable count of Bacillus subtilis is greater than or equal to , and the viable count of white - rot fungi is greater than or equal to .
[0016] Preferably, the specific surface area of the modified biochar is greater than or equal to , the carbon content is greater than or equal to 75%, the porosity is greater than or equal to 60%, and the pore size distribution is 10 nm - 100 μm.
[0017] Preferably, the conditioner is in the form of spherical particles with a particle size of 2-4 mm, a uniformity of greater than or equal to 95%, a breakage rate of less than or equal to 2%, a moisture content of less than or equal to 15%, and a pH value of 6.5-7.5; the nutrient release period of the conditioner is 120 days, in which the first stage is from 0 to 15 days, with a release of 25-30% of the total amount, the second stage is from 16 to 60 days, with a release of 40-50% of the total amount, and the third stage is from 61 to 120 days, with a release of 20-30% of the total amount; the adsorption capacity of the conditioner for heavy metals is: greater than or equal to 150 mg / g, greater than or equal to 80 mg / g, greater than or equal to 120 mg / g.
[0018] The method for preparing the intelligent controlled-release core-shell alginate soil conditioner includes the following steps: (1) Preparation of the core layer: Prepare an aqueous solution of the modified alginate with a concentration of 2-3%, add humic acid and nutrients, and after homogenization treatment at a rotation speed of 10,000 rpm for 5 minutes and ultrasonic treatment at a power of 200 W for 5 minutes, through a coaxial electrospray device with a voltage of 20-25 kV, an inner needle flow rate of 0.5-1.0 mL / h, an outer needle flow rate of 2-4 mL / h, and a collection distance of 15 cm, spray it into a 2% cross-linking solution with a pH of 7.0, stir magnetically at a rotation speed of 200 rpm for 30 minutes, then filter and wash, pre-freeze at a temperature of -40°C for 4 hours, and then perform freeze-drying with a main drying temperature of -20°C for 24 hours; a pressure of 10 Pa to obtain core layer particles; (2) Coating of the middle shell layer: Prepare a 2% solution of chitosan in 1% acetic acid and a 5% solution of gelatin at a temperature of 40°C, mix the two in a mass ratio of 3:1, add a nanozeolite or montmorillonite suspension, after homogenization treatment at a rotation speed of 8000 rpm for 5 minutes, adjust the pH to 5.5, add the core layer particles, stir at a temperature of 30°C, dropwise add a 0.5% TPP solution for ionic cross-linking, and then perform chemical cross-linking with 0.25% glutaraldehyde at a temperature of 25°C for 2 hours, wash and centrifuge, and then freeze-dry to obtain composite particles coated with the middle shell layer; (3) Outer coating: Using the layer-by-layer self-assembly technique, immerse the composite particles obtained in step (2) successively into a modified biochar or bentonite composite suspension with a concentration of 1-2% and a pH of 4.5 for 10 minutes, a polyelectrolyte solution, PAA, with a concentration of 1% and a pH of 7.0 for 10 minutes, and a magnetic nano suspension with a concentration of 0.5% and a pH of 5.5 for 10 minutes, wash and repeat 3-5 times, and finally perform chemical fixation with 0.5% glutaraldehyde for 30 minutes, wash and dry; (4)Forming and post-treatment: The particles obtained in step (3) are pre-frozen at a temperature of -40°C for 4 hours, and then subjected to combined drying, vacuum freeze-drying: the main drying temperature is -20°C for 24 hours; the post-drying temperature is 10°C for 6 hours; microwave-assisted final drying: power 100W, time 2 minutes, intermittent, after cooling, fluidized bed coating and granulation are carried out, the inlet temperature is 45±2°C, a 5% PVA binder solution is sprayed in, the spraying rate is 5-8 mL / min, after drying, surface functionalization treatment is carried out, an anti-caking agent and a biodegradable film-forming agent are used, and after screening and packaging, the finished product is obtained.
[0019] Preferably, the method for preparing the modified alginate in step (1) is: waste seaweed washing → crushing to less than or equal to 2 mm → 1% soaking at a temperature of 80°C for 2 hours → ultrasonic treatment at a frequency of 40 kHz for 30 minutes → cellulase treatment at a temperature of 50°C, pH 5.5 for 4 hours → filtration → precipitation → purification → drying → crushing.
[0020] Preferably, the method for preparing chitosan in step (2) is: shrimp and crab shells → washing → crushing to less than or equal to 1 mm → deproteinization with 1M NaOH at a temperature of 90°C for 1 hour → washing → demineralization with 1M HCl at room temperature for 2 hours → washing → decolorization → deacetylation with 50% NaOH at a temperature of 90°C for 4 hours × 2 times → washing → drying → crushing, and the degree of deacetylation of the obtained chitosan is greater than or equal to 90%.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The beneficial effects of the present invention are as follows: 1. Through the design of the core-shell-layer three-layer structure, multiple functions of precise nutrient supply, efficient heavy metal fixation, and soil microenvironment regulation are realized; 2. Adopting the pH / temperature / microorganism triple response mechanism, the nutrient release is synchronized with the crop growth cycle, significantly improving the nutrient utilization efficiency; 3. Utilizing the high-value utilization of waste seaweed and crustacean shells reduces the raw material cost and meets the requirements of green and sustainable development; 4. Adopting coaxial electrospray and layer-by-layer self-assembly technology simplifies the preparation process and improves the product uniformity and stability; 5. The product shows excellent improvement effects in sandy wasteland and saline-alkali land, with an organic matter increase rate of 40% and a secondary salinization inhibition rate of saline-alkali land reaching 80%. Description of the Drawings
[0022] Figure 1 It is the nutrient release curve diagram of the intelligent controlled-release core-shell type alginate soil conditioner of the present invention.
[0023] Figure 2 This is the test result graph of the heavy metal adsorption performance of the intelligent controlled-release core-shell alginate soil conditioner of the present invention.
[0024] Figure 3 This is the comparative experiment result graph of the intelligent controlled-release core-shell alginate soil conditioner of the present invention for improving sandy soil.
[0025] Figure 4 This is the comparative experiment result graph of the intelligent controlled-release core-shell alginate soil conditioner of the present invention for improving saline-alkali soil.
[0026] Figure 5 This is the morphology graph of the intelligent controlled-release core-shell alginate soil conditioner prepared in Example 1, where 5A is the macroscopic appearance graph, 5B is the SEM image of the cross-section slice of the product, Figure 5 C is the high-magnification SEM image of the outer surface of the product. Detailed implementation manners
[0027] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without making creative efforts shall fall within the protection scope of the present invention.
[0028] Example 1: Preparation of intelligent controlled-release core-shell alginate soil conditioner Preparation of the core layer: (1) Preparation of modified alginate: Take 100 g of waste kelp, wash and chop it, then add 500 mL of 1% solution, heat in a water bath at 80 °C for 2 h, perform ultrasonic treatment (40 kHz, 30 min), cellulase treatment (50 °C, pH 5.5, 4 h), filter, precipitate with ethanol, wash, and dry to obtain modified alginate powder.
[0029] (2) Preparation of core layer particles: Take 2.5 g (50%) of modified alginate, 0.5 g (10%) of humic acid, and nitrogen-phosphorus-potassium compound fertilizer (N: : =15:15:15) 1.0 g (20%), trace element complex (Fe, Mn, Zn, Cu, B, Mo) 0.15 g (3%), auxiliary materials 0.35 g (7%). The auxiliary materials include ascorbic acid (antioxidant) 0.08 g (1.6%), sodium polyacrylate (dispersant) 0.12 g (2.4%), citric acid (pH regulator) 0.06 g (1.2%), polyethylene glycol 6000 (solubilizer) 0.05 g (1.0%), trehalose (protective agent) 0.04 g (0.8%). They are dissolved in 100 mL of deionized water to prepare a mixed solution with a concentration of 2.5%.
[0030] (3) After homogenizing the above mixed solution (10000 rpm, 5 min) and ultrasonic treatment (200 W, 5 min), it is sprayed into a 2% cross-linking solution (pH 7.0) through a coaxial electrospray device (voltage 20 kV, inner needle flow rate 0.5 mL / h, outer needle flow rate 2 mL / h, collection distance 15 cm), and magnetically stirred (200 rpm, 30 min).
[0031] (4) Filter and wash, and after pre-freezing (-40 °C, 4 h), perform freeze-drying (primary drying at -20 °C, 24 h; pressure 10 Pa) to obtain the core layer particles.
[0032] Intermediate shell coating: (1) Preparation of chitosan solution: Take 2.0 g (40%) of chitosan with a deacetylation degree of 90% and dissolve it in 100 mL of 1% acetic acid solution, and stir overnight to obtain a 2% chitosan solution.
[0033] (2) Preparation of gelatin solution: Take 0.75 g (15%) of gelatin and dissolve it in 15 mL of warm water (40 °C) to obtain a 5% gelatin solution.
[0034] (3) Take 0.75 g (15%) of nanozeolite / montmorillonite, microbial preparation (Azospirillum brasilense and Bacillus subtilis, weight ratio 1:1, viable count ≥ 5 × CFU / g) 0.25 g (5%), PLGA 0.25 g (5%), auxiliary materials 0.5 g (10%). The auxiliary materials include potassium dihydrogen phosphate (buffer) 0.15 g (3%), glycerol (plasticizer) 0.12 g (2.4%), potassium sorbate (preservative) 0.08 g (1.6%), polyvinylpyrrolidone K30 (stabilizer) 0.09 g (1.8%), betaine (compatibilizer) 0.06 g (1.2%), and add them to the mixed solution (mass ratio 3:1) of the above chitosan solution and gelatin solution.
[0035] (4) After homogenization (8000 rpm, 5 min), adjust the pH to 5.5, add the core layer particles prepared in step 1, and stir at 30 °C for 30 min.
[0036] (5) Dropwise add 0.5% TPP solution for ionic crosslinking (20 min), and then use 0.25% glutaraldehyde for chemical crosslinking (25 °C, 2 h).
[0037] (6) Wash, centrifuge (3400 rpm, 5 min), and freeze-dry to obtain composite particles coated with the intermediate shell layer.
[0038] Outer layer coating: (1) Preparation of modified biochar: Take straw biochar, obtain powder with a particle size ≤ 100 μm after ball milling, and use activation (100 °C, 2 h), washing, and drying to obtain modified biochar.
[0039] (2) Preparation of magnetic nanoparticles : Using the chemical co-precipitation method, with and as raw materials (molar ratio 2:1), stir at 60 °C under protection, dropwise add NH3 until the pH is 10 - 11, stir at 80 °C for 1 h, wash and dry to obtain nanoparticles with a particle size of 15 - 30 nm particles.
[0040] (3) Disperse 1.5 g (50%) of modified biochar, 0.6 g (20%) of bentonite, 0.15 g (5%) of nanoparticles particles, 0.15 g (5%) of crosslinking agent, and 0.6 g (20%) of auxiliary materials in water to obtain a 1.5% suspension, and adjust the pH to 4.5. Auxiliary materials include 0.14 g (4.7%) of polyvinylpyrrolidone (dispersant), 0.09 g (3%) of sodium dodecyl sulfate (surfactant), 0.12 g (4%) of polyoxyethylene sorbitan monooleate (Tween 80, wetting agent), 0.08 g (2.7%) of sodium carboxymethyl cellulose (thickener), 0.06 g (2%) of sodium glycyrrhizinate (suspending agent), 0.07 g (2.3%) of polyvinyl alcohol (film-forming agent), and 0.04 g (1.3%) of magnesium aluminum metasilicate (anti-caking agent).
[0041] (4) Prepare a polyelectrolyte solution: 1% PAA solution, adjust the pH to 7.0.
[0042] (5) Prepare a magnetic nanoparticle suspension: Disperse the nanoparticle particles in water to obtain a 0.5% suspension, and adjust the pH to 5.5.
[0043] (6) Using the layer-by-layer self-assembly technique, the composite particles obtained in step 2 were successively immersed in the above-mentioned suspension, with an immersion time of 10 min each time, and washed after each immersion. After repeating 3 times, chemical fixation was carried out with 0.5% glutaraldehyde (30 min), followed by washing and drying.
[0044] Forming and post-treatment: (1) The particles obtained in step 3 were pre-frozen (-40 °C, 4 h) and then subjected to composite drying (vacuum freeze-drying: primary drying at -20 °C for 24 h; secondary drying at 10 °C for 6 h; microwave-assisted final drying: 100 W, 2 min, intermittent).
[0045] (2) After cooling, fluidized bed coating granulation was carried out (inlet temperature 45 °C, spraying 5% PVA binder solution, spraying rate 5 mL / min).
[0046] (3) After drying, surface functionalization treatment was carried out, spraying an anti-caking agent (1% talc powder, 0.5% silica) and a degradable film former (1% polyvinyl alcohol, 0.5% glycerol).
[0047] (4) Screening and packaging were carried out to obtain the finished product.
[0048] The final product is spherical particles with a particle size of 2 - 3 mm, a crushing rate ≤ 2%, a moisture content ≤ 10%, and a pH value of 7.0 ± 0.5.
[0049] Example 2: Preparation of intelligent controlled-release core-shell alginate soil conditioner with different ratios According to the method of Example 1, an intelligent controlled-release core-shell alginate soil conditioner with different ratios was prepared, and the formulation composition is shown in Table 1: Table 1 Formulation composition of intelligent controlled-release core-shell alginate soil conditioner with different ratios Component Example 2-1 Example 2-2 Example 2-3 Core layer (total weight 30%) Modified alginate 60% 55% 50% Humic acid 10% 12.50% 15% Nitrogen, phosphorus and potassium compound nutrients 20% 22.50% 25% Trace elements 5% 4% 3% Auxiliary materials 5% 6% 7% Intermediate shell layer (total weight 40%) Chitosan 50% 45% 40% Gelatin 10% 12.50% 15% Nanozeolite / montmorillonite 20% 17.50% 15% Microbial agent 5% 7.50% 10% PLGA 10% 7.50% 5% Auxiliary materials 5% 10% 15% Outer layer (total weight 30%) Modified biochar 50% 45% 40% Bentonite 20% 25% 30% <![CDATA[Magnetic nano-Fe3O4]]> 10% 7.50% 5% Crosslinking agent 5% 7.50% 10% Auxiliary materials 15% 15% 15% The preparation method was the same as that of Example 1, but the proportions of each component and the corresponding dosages were adjusted.
[0050] Example 3: Preparation of intelligent controlled-release core-shell alginate soil conditioner under different process parameters According to the formulation of Example 1, an intelligent controlled-release core-shell alginate soil conditioner was prepared under different process parameters, and the process parameters are shown in Table 2: Table 2 Preparation conditions of intelligent controlled-release core-shell alginate soil conditioner under different process parameters Process parameters Example 3-1 Example 3-2 Example 3-3 Core layer preparation Alginate concentration 2% 2.50% 3% Electrospray voltage 20 kV 22.5 kV 25 kV Inner needle flow rate 0.5 mL / h 0.75 mL / h 1.0 mL / h Outer needle flow rate 2 mL / h 3 mL / h 4 mL / h <![CDATA[CaCl2 concentration]]> 2% 2% 2% Intermediate shell layer coating Chitosan concentration 2% 2% 2% Gelatin concentration 5% 5% 5% TPP concentration 0.50% 0.50% 0.50% Glutaraldehyde concentration 0.25% 0.25% 0.25% Crosslinking time 1h 2h 3h Outer layer coating Suspension concentration 1% 1.50% 2% Soaking time 5 min 10 min 15 min Repetition times 3 4 5 Drying conditions Pre-freezing temperature -40℃ -40℃ -40℃ Primary drying temperature -20℃ -20℃ -20℃ Primary drying time 24h 24h 24h Microwave power 100W 100W 100W The preparation method was the same as that of Example 1, but the process parameters of each step were adjusted.
[0051] Example 4: Intelligent controlled-release core-shell soil conditioner prepared by different modified alginate preparation methods According to the formula and process parameters of Example 1, different methods were used to prepare improved alginate, which was then used to prepare the intelligent controlled-release core-shell soil conditioner: Example 4-1: The modified alginate was prepared by acid extraction: 100 g of discarded kelp was washed and chopped, and then 500 mL of 0.1 M HCl solution was added, stirred at room temperature for 2 h, filtered, and the residue was treated with 0.1 M The solution was extracted (80°C, 3h), filtered, precipitated with ethanol, washed, and dried to obtain the modified alginate powder.
[0052] Example 4-2: The improved alginate was prepared by the enzyme-ultrasound synergistic method: 100 g of discarded kelp was taken, washed and chopped, and then 500 mL of pH 7.0 phosphate buffer was added, and cellulase (0.5%) and alginate (0.2%) were added. The mixture was enzymatically hydrolyzed at 45°C for 6 h, and intermittently ultrasonicated (40 kHz, 10 min per hour), filtered, precipitated with ethanol, washed, and dried to obtain the improved alginate powder.
[0053] Example 4-3: Improved alginate was prepared by microwave-assisted extraction: 100 g of discarded kelp was washed and chopped, and then 1% 500 mL of the solution was treated with microwaves (500 W, 5 min), filtered, the residue was treated with microwaves again (500 W, 5 min), filtered, the filtrates were combined, precipitated with ethanol, washed, and dried to obtain the improved alginate powder.
[0054] The properties of the improved alginate prepared in each embodiment are shown in Table 3: Table 3 Characteristics of modified alginate prepared by different methods Characteristic parameters Example 4-1 Example 4-2 Example 4-3 Extraction rate 18% 22% 20% M / G ratio 1.2 1.3 1.5 Molecular weight (kDa) 80-100 60-80 70-90 Viscosity (1% solution, mPa·s) 350 300 320 Purity 85% 90% 88% The subsequent preparation steps are the same as those in Example 1.
[0055] Example 5: Intelligent controlled-release core-shell alginate soil conditioner with different microbial preparation combinations According to the formulation and process parameters of Example 1, different microbial preparation combinations were added to the intermediate shell layer: Example 5-1: The microbial preparation combination is a mixture of Azospirillum brasiliensis and Bacillus subtilis, and the number of viable bacteria is , the mixing ratio is 1:1.
[0056] Example 5-2: The microbial agent combination is a mixture of Bacillus subtilis, white rot fungi and phosphorus-solubilizing bacteria, and the viable count of each is , and the mixing ratio is 1:1:1.
[0057] Example 5-3: The microbial agent combination is a mixture of photosynthetic bacteria, Azospirillum and actinomycetes, and the viable count of each is , and the mixing ratio is 1:1:1.
[0058] The subsequent preparation steps are the same as those in Example 1.
[0059] Example 6: Intelligent controlled-release core-shell alginate soil conditioner with different outer layer component ratios According to the core layer and middle shell layer formula and process of Example 1, adjust the outer layer component ratio to prepare intelligent controlled-release core-shell alginate soil conditioners with different outer layer component ratios: Example 6-1: Outer layer composition: 40% modified biochar, 30% bentonite, 10% magnetic nanoparticles , 5% cross-linking agent, 15% auxiliary material.
[0060] Example 6-2: Outer layer composition: 45% modified biochar, 25% bentonite, 7.5% magnetic nanoparticles , 7.5% cross-linking agent, 15% auxiliary material.
[0061] Example 6-3: Outer layer composition: 50% modified biochar, 20% bentonite, 5% magnetic nanoparticles , 10% cross-linking agent, 15% auxiliary material.
[0062] The subsequent preparation steps are the same as those in Example 1.
[0063] Comparative Example 1: Simple mixed soil conditioner without core-shell structure Mix 15% modified alginate, 20% chitosan, 5% humic acid, 10% nitrogen, phosphorus and potassium composite nutrients, 1.5% trace elements, 15% biochar, 10% bentonite, 3% microbial agent, magnetic nanoparticles 2% and 18.5% auxiliary material directly, and obtain the comparative product through granulation, drying and screening.
[0064] The total feeding amount is the same as that in Example 1, but the core-shell structure is not adopted, and all components are directly mixed.
[0065] Comparative Example 2: Soil conditioner with only core-shell structure and no outer layer According to the method of Example 1, only the soil conditioner with a core layer and an intermediate shell layer is prepared, without adding an outer layer.
[0066] Composition of the core layer (40% of the total weight): Modified alginate 55%, Humic acid 12.5%, Nitrogen-phosphorus-potassium compound nutrients 22.5%, Trace elements 4%, Auxiliary materials 6%.
[0067] Composition of the intermediate shell layer (60% of the total weight): Chitosan 45%, Gelatin 12.5%, Nanozeolite / montmorillonite 17.5%, Microbial preparation 7.5%, PLGA 7.5%, Auxiliary materials 10%.
[0068] Comparative Example 3: Core-shell type soil conditioner prepared by the ordinary water bath emulsification method According to the formulation composition of Example 1, a core-shell type soil conditioner was prepared by using the traditional water bath emulsification method instead of the coaxial electrospray technology: The modified alginate solution was mixed with nitrogen-phosphorus-potassium compound nutrients and trace elements, and was dropped into the cross-linking solution containing 2% under high-speed stirring (8000 rpm) to form alginate gel beads. The gel beads were transferred to the chitosan solution and soaked for 2 h to form a chitosan coating layer. The subsequent steps were the same as those in Example 1.
[0069] VI. Performance testing and application effects 6.1 Product characterization Please refer to Figure 5 , for the morphological and structural characterization: The product prepared in Example 1 presented regular spherical shapes, with a smooth surface and uniform particle sizes of 2 - 3 mm; the interfaces between the core layer, the intermediate shell layer, and the outer layer were clear, and the structure was complete. The product of Comparative Example 3 had irregular shapes, uneven particle size distributions, different sizes, and blurred interfaces.
[0070] Figure 5 A shows the macroscopic morphological characteristics of the product in Example 1. It can be observed that the product presents highly regular spherical particles, with a smooth surface and uniform gloss, and the diameters are mainly distributed in the range of 2 - 3 mm. The size differences between the particles are small, the shape regularity is high, the appearance consistency is good, and there are no obvious deformations or damages. The particle surface has a fine texture structure, which is a characteristic surface topography formed during the outer layer coating process. The 10 mm scale shows the actual size of the particles, facilitating the intuitive judgment of the product specifications. This uniform spherical structure is beneficial to the uniform distribution and stable release of the product in the soil.
[0071] Figure 5 B is the SEM image of the cross-section slice of the product, clearly showing the core-shell-layer three-layer structure of the product. From the outside to the inside, it can be observed in turn: Outer layer: It has a dense structure, with an obvious roughness on the surface. Uniformly distributed black granular substances can be seen, which are magnetic nanoparticles (particle size 15 - 30 nm). The interface between the outer layer and the middle shell layer is clear, and they are tightly combined without gaps.
[0072] Middle shell layer: It presents a typical reticular cross-linked structure, and the three-dimensional network formed by chitosan and gelatin is clearly visible. The pore sizes in the network structure are uniform, with a diameter of about 1 - 2 μm. This structure is beneficial to the selective permeation of substances and environmental response performance.
[0073] Core layer: It has a diameter of about 80 μm and presents a porous sponge-like structure. The pore sizes are between 5 - 10 μm, and the pore connectivity is good. This structure is a cross-linked network formed by modified alginate and humic acid, which is beneficial to the storage and slow release of nutrients.
[0074] The interfaces between the three layers are clearly distinguishable, and the structure transitions naturally without obvious fractures or detachments, indicating the precision of the preparation process and the good compatibility between the materials. The 50 - μm scale indicates that the observation magnification is appropriate, and the microscopic features of the three-layer structure can be clearly distinguished.
[0075] Figure 5 C shows a high-magnification SEM image of the surface of the product outer layer. It can be observed that the surface has an obvious micro-nano rough structure, presenting a characteristic "hill-valley" morphology. Black nanoparticles (magnetic nanoparticles ) with a diameter of about 3 - 4 μm are uniformly distributed on the surface, and the particle spacing is about 5 - 10 μm. The distribution density is moderate, and no obvious agglomeration phenomenon is seen. Tiny wrinkles and grooves can also be observed on the surface, forming a multi-level surface roughness. This multi-level rough structure significantly increases the specific surface area (≥500 m² / g), providing abundant active sites for heavy metal ion adsorption. The 10 - μm scale shows the microscopic scale of the observation, making the surface microscopic structure features clearly visible.
[0076] For the product obtained in Example 1, the particles in the particle size range of 2 - 3 mm have the highest proportion, reaching about 70%, which is the main particle size distribution range of the product. The particle size range of 3 - 4 mm comes second, accounting for about 20%. The particle size range of 1 - 2 mm comes next, accounting for about 5%. The larger particle size particles in the ranges of 4 - 5 mm and 5 - 6 mm have a very small proportion, about 3% and 2% respectively. This concentrated particle size distribution (70% in the 2 - 3 mm range) and high uniformity (≥95%) indicate that the preparation process of the present invention has a high degree of controllability and repeatability, and can stably produce products meeting the requirements. The moderate particle size is beneficial to the uniform distribution and stable release of the product in the soil, and is also convenient for agricultural mechanized application, improving the application efficiency.
[0077] Physicochemical property characterization: The pH value of the product prepared in Example 1 is 7.0 ± 0.5, the moisture content is 8.5%, the mechanical strength is > 20 N, and the bulk density is 0.85 , and the specific surface area is 550 , and the porosity is 65%. The product has good water resistance. After being soaked in water for 24 h, its structure remains intact and there is no obvious swelling.
[0078] Determination of nutrient content: The total nutrient content ( ) of the product prepared in Example 1 is 15.5%, the organic matter content is 42.5%, and the total amount of trace elements is 2.2%, among which Fe is 0.8%, Zn is 0.4%, Mn is 0.4%, Cu is 0.2%, B is 0.3%, and Mo is 0.1%.
[0079] 6.2 Nutrient release performance test The nutrient release of different samples was determined by the leaching method. 1 g of the sample was placed in 100 mL of deionized water, and the contents of N, P, and K in the solution were measured under different conditions to draw the nutrient release curve.
[0080] pH-responsive release test: The nutrient release was measured under the conditions of pH 5.5, 6.5, and 7.5. The results showed that: under the condition of pH 5.5, the nutrient release rate of the sample in Example 1 was significantly higher than that under the condition of pH 7.5, and the release rate difference coefficient was 2.5, showing obvious pH responsiveness; while the pH responsiveness of the samples in Comparative Example 1 and Comparative Example 3 was weak, and the release rate difference coefficient was only 1.2 - 1.4.
[0081] Temperature-responsive release test: The nutrient release was measured under the conditions of 10 °C, 20 °C, and 30 °C. The results showed that: under the condition of 30 °C, the nutrient release rate of the sample in Example 1 was significantly higher than that under the condition of 10 °C, and the release rate difference coefficient was 1.8, showing obvious temperature responsiveness; while the temperature responsiveness of the samples in Comparative Example 1 and Comparative Example 3 was weak, and the release rate difference coefficient was only 1.1 - 1.3.
[0082] Microbial-responsive release test: The nutrient release was measured under the conditions of adding and not adding soil microorganisms. The results showed that: under the condition of adding microorganisms, the nutrient release rate of the sample in Example 1 was significantly accelerated, and the release rate difference coefficient was 2.2, showing obvious microbial responsiveness; while the microbial responsiveness of the samples in Comparative Example 1 and Comparative Example 3 was weak, and the release rate difference coefficient was only 1.2 - 1.3.
[0083] Nutrient retention test: Figure 1The nutrient release curve of the intelligent controlled-release core-shell alginate soil conditioner of the present invention is shown. Through a long-term release experiment of 120 days, the sample of Example 1 showed excellent nutrient persistence, and the release curve showed a three-stage release mode: 28% of the total amount was released in the first stage (0 - 15 days), 45% of the total amount was released in the second stage (16 - 60 days), and 27% of the total amount was released in the third stage (61 - 120 days); while the samples of Comparative Example 1 and Comparative Example 3 released 60 - 70% of the total amount in the first 15 days, without obvious persistence. The samples of Comparative Example 1 and Comparative Example 3 lacked this precisely controlled release mode and released most of the nutrients in the first 15 days.
[0084] 6.3 Heavy metal adsorption performance test The batch adsorption method was used to determine the adsorption performance of different samples for heavy metals. 0.5 g of the sample was placed in a solution containing different concentrations of heavy metals ( ), shaken at 25 °C for 24 h, the residual heavy metal content in the solution was measured, and the adsorption capacity was calculated.
[0085] Figure 2 The test results of the adsorption performance of the present invention for different heavy metals are shown. The results show that: the maximum adsorption capacities of the sample of Example 1 for , , were 180 mg / g, 95 mg / g, and 130 mg / g respectively, which were significantly higher than those of the samples of Comparative Example 1 and Comparative Example 3 (85 mg / g, 40 mg / g, 65 mg / g for Comparative Example 1 respectively; 120 mg / g, 60 mg / g, 90 mg / g for Comparative Example 3 respectively). The adsorption isotherm of the sample of Example 1 conforms to the Langmuir model, indicating monolayer adsorption; the kinetics conforms to the pseudo-second-order kinetic model, indicating the existence of a chemisorption process. The maximum adsorption capacities of the sample of Example 1 for , , were significantly higher than those of the comparative products, proving the advantages of the present invention in the remediation of heavy metal pollution.
[0086] The adsorption mechanism study shows that: the adsorption mechanism of the sample of Example 1 for heavy metals includes ion exchange, complexation chelation, and electrostatic adsorption, in which the carboxyl group of the modified alginate, the amino group of chitosan, and the magnetic capture of magnetic nanoparticles act together to achieve efficient adsorption and stable fixation.
[0087] 6.4 Soil improvement effect test Sandy soil improvement experiment: Add different samples at a dosage of 5 g / kg in sandy soil and measure the physical and chemical properties of the soil after 60 days of cultivation. The results show that after the treatment with the sample of Example 1, the soil organic matter content increased by 40%, the water retention capacity increased by 35%, the fertilizer retention capacity increased by 42%, and the stability of soil aggregate structure increased by 38%; while the improvement effects of the samples of Comparative Example 1 and Comparative Example 3 were 22-25% and 30-32% respectively.
[0088] Saline-alkali land improvement experiment: Add different samples at a dosage of 7 g / kg in saline-alkali soil and measure the physical and chemical properties of the soil after 90 days of cultivation. The results show that after the treatment with the sample of Example 1, the inhibition rate of soil secondary salinization reached 80%, the pH decreased by 0.8 units, the soil electrical conductivity decreased by 45%, and the soil aeration increased by 36%; while the improvement effects of the samples of Comparative Example 1 and Comparative Example 3 were 45-48% and 60-65% respectively.
[0089] Heavy metal contaminated soil remediation experiment: Add different samples at a dosage of 10 g / kg in the soil contaminated with Pb, Cd, and Cu composites and measure the available content of heavy metals in the soil after 120 days of cultivation. The results show that after the treatment with the sample of Example 1, the available contents of Pb, Cd, and Cu in the soil decreased by 85%, 78%, and 82% respectively; while the fixation efficiencies of the samples of Comparative Example 1 and Comparative Example 3 were 40-45% and 60-65% respectively.
[0090] Figure 3 and Figure 4 respectively show the effects of the present invention in improving sandy soil and saline-alkali soil. In terms of sandy soil improvement, the sample of Example 1 showed significant advantages in three key indicators: organic matter increment, water retention capacity, and aggregate structure; in terms of saline-alkali soil improvement, the salt inhibition rate of the sample of Example 1 was as high as 80%, and the effect was significantly better than that of the comparative example products.
[0091] 6.5 Crop growth effect test Plant wheat, corn, and rice in the improved soil and investigate the effects of different samples on crop growth. The results show that: Wheat growth experiment: After the treatment with the sample of Example 1, the wheat yield increased by 28%, the thousand-grain weight increased by 15%, and the protein content increased by 12%; while the yield increase effects after the treatment with the samples of Comparative Example 1 and Comparative Example 3 were 15-17% and 20-22% respectively.
[0092] Corn growth experiment: After the sample treatment in Example 1, the corn yield increased by 32%, the ear length increased by 18%, and the 100-kernel weight increased by 14%; while the yield-increasing effects after the sample treatments in Comparative Example 1 and Comparative Example 3 were 18 - 20% and 23 - 25% respectively.
[0093] Rice growth experiment: After the sample treatment in Example 1, the rice yield increased by 25%, the seed setting rate increased by 16%, and the 1000-kernel weight increased by 12%; while the yield-increasing effects after the sample treatments in Comparative Example 1 and Comparative Example 3 were 14 - 16% and 18 - 20% respectively.
[0094] Through the preparation and testing of the above examples and comparative examples, it is proved that the intelligent controlled-release core-shell alginate soil conditioner of the present invention has the following advantages: 1. Adopting a three-layer structure design of core-shell-layer, it realizes multiple functions of precise nutrient supply, efficient heavy metal fixation, and soil microenvironment regulation; 2. Having a triple response mechanism of pH / temperature / microorganism, enabling the nutrient release to be synchronized with the crop growth cycle and increasing the nutrient utilization efficiency by more than 30%; 3. Having a high-efficiency adsorption and fixation ability for heavy metals, with the adsorption capacity increased by more than 100% compared with traditional materials; 4. Having a significant improvement effect on sandy soil and saline-alkali land, with the organic matter promotion rate reaching 40% and the inhibition rate of secondary salinization of saline-alkali land reaching 80%; 5. Having an obvious promoting effect on the growth of crops, with the yield increase ranging from 25% to 32%.
[0095] The present invention provides a new technical solution for solving problems such as soil infertility, heavy metal pollution, and salinization in China, and has broad application prospects.
[0096] The above are only the embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the scope of the claims of the present invention.
Claims
1. Smart controlled-release core-shell type alginate soil conditioner, characterized in that, The conditioner has a core-shell-layer three-layer structure and comprises components in the following weight percentages: A. The core layer accounts for 30% of the total weight and includes: a) 50 - 60% of modified alginate; b) 10 - 15% of humic acid; c) 20 - 25% of nitrogen, phosphorus and potassium composite nutrients; d) 3 - 5% of trace elements; e) 5 - 10% of auxiliary materials; B. The middle shell layer accounts for 40% of the total weight and includes: a) 40 - 50% of chitosan with a deacetylation degree of greater than or equal to 90%; b) 10 - 15% of gelatin; c) 15 - 20% of nanozeolite or montmorillonite; d) 5 - 10% of microbial agents; e) 5 - 10% of poly(lactic-co-glycolic acid); f) 5 - 10% of auxiliary materials; C. The outer layer accounts for 30% of the total weight and includes: a) 40 - 50% of modified biochar; b) 20 - 30% of bentonite; c) Magnetic nanoparticles Particles 5 - 10%; d) 5 - 10% of cross-linking agent; e) 10 - 15% of auxiliary materials.
2. The smart controlled-release core-shell type alginate soil conditioner according to claim 1, characterized in that, The M / G ratio of the modified alginate is 1.2 - 1.5, the viscosity of its 1% aqueous solution is greater than or equal to 300 mPa·s, and the organic matter content is 35 - 45%.
3. The smart controlled-release core-shell type alginate soil conditioner according to claim 1, characterized in that, The microbial agent includes at least one of Azospirillum brasilense, Bacillus subtilis and white rot fungi, wherein the viable count of Azospirillum brasilense is greater than or equal to , the viable count of Bacillus subtilis is greater than or equal to , and the viable count of white rot fungi is greater than or equal to .
4. The smart controlled-release core-shell type alginate soil conditioner according to claim 1, characterized in that, The specific surface area of the modified biochar is greater than or equal to , the carbon content is greater than or equal to 75%, the porosity is greater than or equal to 60%, and the pore size distribution is 10 nm - 100 μm.
5. The smart controlled-release core-shell type alginate soil conditioner according to claim 1, characterized in that, The conditioner is in the form of spherical particles with a particle size of 2 - 4 mm, a uniformity of greater than or equal to 95%, a breakage rate of less than or equal to 2%, a moisture content of less than or equal to 15%, and a pH value of 6.5 - 7.5; the nutrient release period of the conditioner is 120 days, in which in the first stage, 0 - 15 days, 25 - 30% of the total amount is released, in the second stage, 16 - 60 days, 40 - 50% of the total amount is released, and in the third stage, 61 - 120 days, 20 - 30% of the total amount is released; the adsorption capacity of the conditioner for heavy metals is: Pb²⁺ greater than or equal to 150 mg / g, greater than or equal to 80 mg / g, greater than or equal to 120 mg / g.
6. A method for preparing the smart controlled-release core-shell type alginate soil conditioner according to any one of claims 1-5, characterized in that, It includes the following steps: (1)Preparation of the core layer: Prepare an aqueous solution of the modified alginate with a concentration of 2-3%, add humic acid and nutrients, and conduct homogenization treatment at a rotation speed of 10,000 rpm for 5 minutes and ultrasonic treatment at a power of 200 W for 5 minutes. Then, through a coaxial electrospray device with a voltage of 20-25 kV, an inner needle flow rate of 0.5-1.0 mL / h, an outer needle flow rate of 2-4 mL / h, and a collection distance of 15 cm, spray it into a 2% crosslinking solution with a pH of 7.0, and conduct magnetic stirring at a rotation speed of 200 rpm for 30 minutes. Then, filter and wash, pre-freeze at a temperature of -40°C for 4 hours, and then perform freeze-drying at a main drying temperature of -20°C for 24 hours; the pressure is 10 Pa to obtain core layer particles; (2) Coating of the middle shell layer: Prepare a 2% solution of chitosan in 1% acetic acid, and a 5% solution of gelatin at 40°C. Mix the two according to a mass ratio of 3:1, add a suspension of nanozeolite or montmorillonite, and perform homogenization treatment at a rotation speed of 8000 rpm for 5 min. Then adjust the pH to 5.5, add the core layer particles, stir at 30°C, dropwise add a 0.5% TPP solution for ionic cross-linking, and then perform chemical cross-linking with 0.25% glutaraldehyde at 25°C for 2 h. After washing, centrifugal separation and freeze-drying, composite particles coated with the middle shell layer are obtained; (3) Outer coating: Using the layer-by-layer self-assembly technique, the composite particles obtained in step (2) are successively immersed in a modified biochar or bentonite composite suspension with a concentration of 1-2%, pH 4.5, for 10 min, a polyelectrolyte solution, PAA, with a concentration of 1%, pH 7.0, for 10 min, and a magnetic nano suspension with a concentration of 0.5%, pH 5.5, for 10 min. After washing, repeat 3-5 times. Finally, chemically fix with 0.5% glutaraldehyde for 30 min, wash, and dry; (4) Molding and post-treatment: Pre-freeze the particles obtained in step (3) at -40°C for 4 h, and then perform composite drying, vacuum freeze-drying: the main drying temperature is -20°C for 24 h; the post-drying temperature is 10°C for 6 h; microwave-assisted final drying: power 100 W, time 2 min, intermittent. After cooling, perform fluidized bed coating granulation, with an inlet temperature of 45 ± 2°C, spray in a 5% PVA binder solution at a spraying rate of 5 - 8 mL / min. After drying, perform surface functionalization treatment with an anti-caking agent and a biodegradable film-forming agent, and then sieve and package to obtain the finished product.
7. The method according to claim 6, characterized in that, The method for preparing the modified alginate in step (1) is as follows: waste seaweed is washed → crushed to a size less than or equal to 2 mm → soaked in 1% at a temperature of 80 °C for 2 h → ultrasonic treatment at a frequency of 40 kHz for 30 min → cellulase treatment at a temperature of 50 °C, pH 5.5 for 4 h → filtration → precipitation → purification → drying → pulverization.
8. The method according to claim 6, wherein The method for preparing chitosan in step (2) is: shrimp and crab shells → cleaning → crushing to less than or equal to 1 mm → deproteinization with 1M NaOH at 90°C for 1 h → washing → demineralization with 1M HCl at room temperature for 2 h → washing → decolorization → deacetylation with 50% NaOH at 90°C for 4 h × 2 times → washing → drying → crushing. The deacetylation degree of the obtained chitosan is greater than or equal to 90%.
9. The method according to claim 6, wherein The method for preparing the modified biochar in step (3) is as follows: straw raw material → crushed to less than or equal to 5 mm → low-temperature pyrolysis at a temperature of 400 - 600 °C under nitrogen protection for 1 - 2 h → cooling → ball milling using a planetary ball mill at a rotational speed of 300 rpm for 4 h → screening to less than or equal to 100 μm → functional modification, activation at a temperature of 100 °C for 2 h → washing → drying.
10. The method according to claim 6, wherein The method for preparing magnetic nanoparticles in step (3) is as follows: Using and as raw materials with a molar ratio of 2:1, adopting the chemical coprecipitation method, stirring at 60 °C under the protection of , dropping until the pH reaches 10 - 11, stirring at 80 °C for 1 h, washing, drying, and then performing surface coating modification with chitosan to obtain magnetic nanoparticles with a particle size of 15 - 30 nm and a magnetic saturation intensity greater than or equal to 60 emu / g.
Citation Information
Patent Citations
Chitosan controlled release fertilizer microspheres and preparation method thereof
CN104311253A
Novel method for preparation of chitosan nano carrier and functionalization thereof
CN101766820A
Cation adsorption and controlled fertilizer release double-function biochar microsphere and preparation method thereof
CN105498651A
Preparation method of soil conditioner based on layer-by-layer self-assembled microspheres
CN109054846A
Multi-layer composite fertilizer granule special for saline-alkali land improvement and preparation method thereof
CN110452054A
Cited By
Multifunctional water purifying gel material and preparation method thereof
CN120383353A
A multifunctional water-purifying gel material and preparation method thereof
CN120383353B
A saline-alkali land improver and preparation method thereof
CN120536140B
Enhanced double-layer coated nano mineral soil conditioner and preparation method thereof
CN121555204A